2013
DOI: 10.1007/s00402-013-1713-x
|View full text |Cite
|
Sign up to set email alerts
|

Early migration characteristics of a 180° porous-coated cup with 1-mm press fit

Abstract: Surgeons may expect to find a variable amount of early migration when using the Pinnacle cup. To our knowledge, these are the first results, which show an early "impaction" of a cementless cup, followed by subsequent osseointegration. We believe that an appropriate long-term outcome of the investigated cup is ensured. The data of the present investigation will provide clinicians with useful baseline information with which to compare new cup designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Stihsen et al [20] showed a mean total migration of 1.1 mm for the Pinnacle acetabular cup after 2 years follow-up in 57 Pinnacle cups. Given the established threshold of > 1 mm within 2 years as significant migration of an uncemented cup, Stihsen et al found that 40.4% of their cups migrated more than 1 mm in the observed 2-year follow-up [20]. Our results with cup migration are well in line with the results published by Stihsen et al [20].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stihsen et al [20] showed a mean total migration of 1.1 mm for the Pinnacle acetabular cup after 2 years follow-up in 57 Pinnacle cups. Given the established threshold of > 1 mm within 2 years as significant migration of an uncemented cup, Stihsen et al found that 40.4% of their cups migrated more than 1 mm in the observed 2-year follow-up [20]. Our results with cup migration are well in line with the results published by Stihsen et al [20].…”
Section: Discussionmentioning
confidence: 97%
“…Given the established threshold of > 1 mm within 2 years as significant migration of an uncemented cup, Stihsen et al found that 40.4% of their cups migrated more than 1 mm in the observed 2-year follow-up [20]. Our results with cup migration are well in line with the results published by Stihsen et al [20]. We can report a mean total migration of 1.2 mm after 2 years, with 46.8% of our cups having migrated > 1 mm at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, unscientific findings like those reported in the PIN Study can spread through the literature like ink in milk. According to the Web of Science as of July 2017, 27 publications directly cite PIN Study publications (Bernasek et al 2013;Burge et al 2015;Dhotare et al 2016;Greiner et al 2016;Hosny et al 2013;Klingenstein et al 2012Klingenstein et al , 2013Lainiala et al 2014;Langton et al 2016;Liudahl et al 2013;Lohmann et al 2013;Lombardi et al 2015;Maloney, Ha, and Miller 2015;Matharu et al 2014;Mihalko et al 2014;Plummer et al 2016;Reito et al 2016;Ricciardi et al 2016;Schmitz et al 2013;Singh et al 2013Singh et al , 2015Stihsen et al 2013;Stryker et al 2015;Tsukagoshi et al 2015;Tvermoes et al 2015;Wagner et al 2012;Wyles et al 2014). J&J/DePuy also included PIN Study publications in their 2012 presentation to the FDA on the safety of Metal-on-Metal hip implants, suggesting the potential for mismanaged and manipulated seeding trials to influence regulatory decision making (Voorhorst 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] En nuestra experiencia utilizamos 1 mm de underreaming con una copa completamente hemisférica y no elíptica técnica validada en la literatura para el implante que utilizamos. [30][31][32] En nuestro caso, el componente de prueba es considerado imprescindible para estos pacientes, para asegurarse que la cantidad de injerto a utilizar en el fondo es adecuada. La abducción y la anteversión de la copa las verificamos con la técnica de Meftah-Ranawat.…”
Section: Preparación Del Acetábulounclassified